JURIDICAL REVIEW ON COMMUNITY ROLE IN SPATIAL PLANNING IN EAST LOMBOK REGENCY - Muh. Asy’ari (Fakultas Hukum Universitas Mataram, 2014)
Regulations related to spatial planning of modern city in Indonesia can be seen when Jayakarta,later named Batavia was controlled by the Dutch in the early 7th century. The regulationswere then developed intensively in the early 20th century in view that spatial planning relatesto all aspects of life so that it is necessary for the people to gain access to the spatial planningprocess because the basic concept of spatial planning is stated in paragraph 4 of UUD 1945 andcommunity participation in spatial planning is regulated in Law No. 26 of 2007 concerningSpatial Planning. It is also regulated under government regulation No. 15 of 2010 concerningPublic Participation in Spatial Planning. To direct the development in East Lombok Regencyby utilizing the area efficiently, effectively, harmoniously, proportionally and sustainablyin order to create an equitable East Lombok society, a spatial plan should be developed. Theimplementation of spatial planning includes spatial planning process, space utilization andspace control as a manifestation of the long-term development plan of East Lombok Regency.Keywords : Spatial Planning and Community Role